2020
DOI: 10.3390/cancers12071966
|View full text |Cite
|
Sign up to set email alerts
|

Combined C-Reactive Protein and Novel Inflammatory Parameters as a Predictor in Cancer—What Can We Learn from the Hematological Experience?

Abstract: The acute phase reaction is a systemic response to acute or chronic inflammation. The serum level of C-reactive protein (CRP) is the only acute phase biomarker widely used in routine clinical practice, including its uses for prognostics and therapy monitoring in cancer patients. Although Interleukin 6 (IL6) is a main trigger of the acute phase reactions, a series of acute phase reactants can contribute (e.g., other members in IL6 family or IL1 subfamily, and tumor necrosis factor α). However, the experience fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(55 citation statements)
references
References 137 publications
0
47
0
Order By: Relevance
“…We cannot exclude the possibility that inflammaging (i.e., inflammation associated with aging, see [ 50 ]) or other chronic inflammatory diseases contributed to the observed acute phase reaction. However, we did not perform any additional selection of patients included in our present cytokine studies.…”
Section: Discussionmentioning
confidence: 99%
“…We cannot exclude the possibility that inflammaging (i.e., inflammation associated with aging, see [ 50 ]) or other chronic inflammatory diseases contributed to the observed acute phase reaction. However, we did not perform any additional selection of patients included in our present cytokine studies.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory parameters are considered as possible prognostic markers in several human malignancies [ 9 , 55 ]. These parameters include both acute phase proteins and peripheral blood concentrations of various leukocyte subsets and platelets [ 62 , 72 , 73 , 74 , 75 ]. Increased leukocyte and platelet counts were also seen for several of our HNSCC patients, and we observed significant correlations between IL6 levels, WBC counts, and CRP levels.…”
Section: Discussionmentioning
confidence: 99%
“…Further studies including a larger number of patients and alternative mediator combinations should therefore be encouraged to verify our present results and to identify the optimal combination of mediators for prognostication. Systemic levels of inflammatory mediators have been included in prognostic indices together with other (e.g., clinical) parameters for various inflammatory conditions, including malignant diseases [ 62 ]. Our present study and our ROC analyses suggest that relevant cut-off levels can be identified and can then be used to design a prognostic index for patients with HPV-negative HNSCC, but the number of patients in our present study is too low to allow a suggestion of the exact cut-off values to be used in such a prognostic index.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies of patients with various malignancies have shown that the acute phase reaction, i.e., systemic inflammatory responses, have an adverse prognostic impact in several malignancies, including certain hematological malignancies [ 66 ]. However, systemic inflammatory activity has not been used for prognostication in human AML.…”
Section: Aml Heterogeneity and Prognostic Evaluationmentioning
confidence: 99%